2010 Proceedings of the 56th IEEE Holm Conference on Electrical Contacts 2010
DOI: 10.1109/holm.2010.5619519
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Physical Characterization of Micro-Contact Materials for MEMS Switches

Abstract: A systematic comparison between several pairs of contact materials based on an innovative methodology early developed at NOVA MEMS is hereby presented. The technique exploits a commercial nanoindenter coupled with electrical measurements, and test vehicles specially designed in order to investigate the underlying physics driving the surface-related failure modes. The study provides a comprehensive understanding of micro-contact behavior with respect to the impact of low-to medium levels of electrical current. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
(20 reference statements)
1
28
0
Order By: Relevance
“…The experimental measurement in [23] showed that the Au/Ru bimetallic contact had the contact resistance of 1.9 Ω at the contact force of 145 µN and the current of 1 mA. This value leads to the contact radius of 13 nm with the diffusive transport mode.…”
Section: Comparison Againt the Experimental Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The experimental measurement in [23] showed that the Au/Ru bimetallic contact had the contact resistance of 1.9 Ω at the contact force of 145 µN and the current of 1 mA. This value leads to the contact radius of 13 nm with the diffusive transport mode.…”
Section: Comparison Againt the Experimental Resultsmentioning
confidence: 89%
“…Broué et al [23] showed that the bimetallic contact had the advantage of reliability, seeing that the maximum temperature was not localized on the interface of contact, but on the side with higher resistivity [8]. This will be also discussed in this paper.…”
Section: Introductionmentioning
confidence: 92%
“…Hence, a new set-up was developed for the characterization of contact materials used in micro-switches. In previous works the study of the Au/Au, Ru/Ru, and Au/Ru contact resistance, comparing the stability with respect to an increased level of current has been already presented [2][3][4]. The present paper intends to recall these previous results to extend and focus on critical aspects, such as contact asperity, joule-effect-induced heating, and finally contact adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The top radius of the asperity (a) is defined as 120 nm in the modeling, which is based on the finite element mechanical contact modeling [15], with the applied contact force of 150 μN, accordance to the experimental results [16]. And the height of the asperity is defined as h=6 nm and the angle of side as α=10° from the AFM data [14].…”
Section: A Contact Asperity Modelingmentioning
confidence: 99%